Volumetric & Transport Behavior of Neutral Amino Acids in Different Concentrations of an Electrolyte at 25°C - Dhir, Vaneet; Grewal, R. P. Singh (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
Apparent molar volumes, V2, ? of  glycine, DL-?-alanine, DL-?-amino-n-butyric  acid, L-valine and L-leucine in water and in (0.25,  0.5, 0.75, 1.0, 1.5, 2.0) mol?kg-1 aqueous  potassium nitrate solutions have been  determined at T= 298.15 K from density  measurements. The standard partial molar  volumes at infinite dilution, V20 obtained from  V2, ? , have been used to calculate the  corresponding volumes of transfer, ?tV0 from  water to aqueous potassium nitrate solutions.  The hydration number, nH, side chain  contributions and volumetric interaction  coefficients of these amino acids have also been  calculated. The ?tV0 values for the studied amino  acids are positive, and these values increase with  an increase in the concentration of NaNO3 .